School Absenteeism among Children Reflection on Schooling from Rural India - Das, Pankaj (JOURNAL OF INDIAN EDUCATION, 2013)
School absenteeism is one of those close factors which hamper the process of child’s smooth schooling and educational development in the country. The ambit of school absenteeism is a broad one which includes school phobia, school refusal, post registration absence and psychological absence, etc. However, any form of school absenteeism directly or indirectly pushes the child towards downward mobility in the educational ladder of the society. And this phenomenon persists in many of the government schools in the rural pockets of India. Thus, the whole idea or notion of access to education as a fundamental right for these children comes as a major challenge due to the persistence of the high rate of absenteeism in the schools of the country sides. Then what absenteeism really means and how it is interwoven with child schooling along with other associated factors, this present micro study was an attempt to explore the nature, magnitude and complexity of school absenteeism and its impact on schooling in the rural India.